Techno-economic Aspects of Electricity Generation from a Farm Based Biogas Plant - Lina Jarrar; Osama Ayadi; Jamil Al Asfar (Journal of Sustainable Development of Energy, Water and Environment Systems, 2020)

(untitled)
This study produces a technical and economic analysis of a farm- fed biogas plant that utilizes cow manure to produce electricity and heat via combined heat and power unit. The electricity generated is directly injected into the grid while heat is used within the biogas plant. The biogas system design was done depending on number of cows in the farm, which denotes the amount of manure available as feedstock. The economic performance of the proposed biogas plant was evaluated using various economic indicators. The levelized cost of electricity and the avoided greenhouse gas emissions were calculated too. The preliminary design and economic feasibility results proved the profitability of the manure-based biogas systems on wide range of farm sizes. The net present values of a 100-cow, 500-cow, 1,000-cow, 1,500-cow and 2,000-cow farms were all positive. The internal rate of return values were 11%, 12%, 13%, 16% and 17%, respectively, and the levelized cost of electricity values were 0.071, 0.069, 0.064, 0.055 and 0.055 JOD/kWh, respectively. The study also produced a design for a centralized anaerobic digestion plant depending on Jordan resources. The government role in promoting biogas-based electricity was discussed too.